Implementation of Sri Aurobindo’s Philosophy of Education at Primary Level: A Case Study - Davar, Monika Davar (THE PRIMARY TEACHER, 2018)
Sri Aurobindo Ghosh (1872–1950) was one of the greatest philosophers of his time. Sri Aurobindo presented the concept of Integral Education and Principles of True Teaching which has great relevance in the present education system in the context of deteriorating values. The education system if guided by his philosophy can unleash the great potential in each child. The study aims to explore the extent to which a reputed School in Delhi is following Sri Aurobindo’s philosophy at the pre-primary and primary level and its impact on the students. The case study method was used and data obtained were analysed qualitatively to arrive at some significant findings. The outcome was found to be positive and beneficial for primary school students. This study, if followed up with similar research findings in other educational institutions, can lead to a major paradigm shift in the present education system.